Latitudinal variation in population structure and reproductive pattern of the endemic south american shrimp Artemesia longinaris (Decapoda : Penaeoidea) - Castilho, Antonio L.; Gavio, Maria A.; Costa, Rogério Caetano da [UNESP]; Boschi, Enrique E.; Bauer, Rayniond T.; Fransozo, Adilson (Crustacean Soc, 2007)
Population Structure and reproductive Maturity of females were investigated in the shrimp Artemesia longinaris Bate, 1888 from coastal waters of northern São Paulo State (Brazil. 23 degrees S) and Mar del Plata (Argentina, 38 degrees S) from June 2001 to May 2002. Monthly collections were taken by, commercial shrimp fishing boats equipped with bottom trawl nets. Population parameters from size frequency distributions and size (carapace length = CL) of female reproductive maturity were analyzed and compared front the two sampling areas. Latitudinal trends in reproductive parameters of A. longinaris were shown in overall body size and size of reproductive maturity, both of which were smaller in females from the tropical location than those front the cold-temperate sampling area. Largest females (> 30 turn CL) were collected in Argentina, while Brazilian specimens reached maximum size at 27 nun CL. The smallest Size of female sexual maturity was estimated at 13.6 nun CL in Brazilian samples compared to 22.1 mm CL calculated for those from Argentina. Populations from both regions exhibited a bimodal size distribution in the spring, with the peak at small body size probably corresponding to recent recruits and the peak at larger body, size to reproductive females or shrimps migrating in from deeper waters or other latitudinal regions. In late spring and summer. an intrusion of the cold South Atlantic Coastal Water mass was observed which lowered water temperature and stimulated plankton production. The primary food source for the larvae of a typically cold-temperate species such as A. longinaris. The trend of increasing body size and delay of sexual maturity with increasing latitude appears to be correlated with the decreasing water temperature and increasing plankton productivity at higher latitudes.